Evaluation of capacity development activities of CGIAR - Palenberg, Markus; Rauniyar, Ganesh; Thangata, Paul (CGIAR Independent Evaluation Arrangement, 2017)
The Evaluation assessed capacity development (CD) activities across CGIAR at three levels: individual, organizational, and institutional (networks and policies).